Magnetic sheath effect on the gross and net erosion rates due to impurities. (22nd January 2016) - Mellet, N; Pégourié, B; Martin, C; Gunn, J P; Bufferand, H; Roubin, P
Abstract: Simulations of impurity trajectories in deuterium plasmas in the vicinity of the surface are performed by taking into account the magnetic sheath in conditions relevant for ITER and WEST. We show that the magnetic sheath has a strong effect on the average impact angle of impurities in divertor conditions and that it can lead to an increase of at the gross erosion maximum for neon (Ne +4 ) compared to the case when only the cyclotron motion is considered. The evaluation of the net erosion has been undertaken by retaining local redeposition of tungsten (W). We investigate how it is affected by the sheath magnetic potential profile. The largest effect is however observed when an energy distribution is considered. In this case the number of particles that manage to exit the sheath is larger as it is dominated by the more energetic particles. The comparison with other work is also discussed. The application to a scenario of the WEST project is finally performed, which exhibits a moderate, however non negligible, erosion of the plasma facing components.